Non-adhesive Contacts With Different Surface Tension Inside and Outside the Contact Area - Li, Qiang; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2020)
In the past decade, the influence of surface tension on contact properties has attracted much attention, especially in the context of contact of very soft materials (such as gels) or contacts at the nanoscale. However, in the most current studies it is assumed that the tension of the surface inside and outside the contact area is the same. In practical terms, this means that the object considered is an elastic body “coated” with a tensed membrane. In real contacts, there is no reason why the surface tensions of the “free interface” and the “contact interface” should be equal. On the contrary, especially in contacts of soft bodies with hard solid indenters, one can anticipate that they are completely different. In the present article, we consider an elastic contact taking into account different surface tensions inside and outside the contact area. However, the considered contacts are still “non-adhesive.” This means that the three surface energies in play (two surface energies of both bodies outside the contact and the interface energy in the contact region) fulfill the criterion that the work of separation vanishes. A numerical model based on the Fast Fourier transform–assisted boundary element method is implemented and is illustrated with a few examples.